2021
DOI: 10.1155/2021/9923789
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Changes in Tongue Area and Pharyngeal Airway Space following Mandibular Setback Surgery through Intraoral Vertical Ramus Osteotomy

Abstract: Purpose. The aim of this study was to determine changes in the tongue area and pharyngeal airway space (PAS) after intraoral vertical ramus osteotomy (IVRO). Materials and Methods. Serial lateral cephalograms of 40 patients with mandibular prognathism who underwent IVRO were evaluated before (T1), immediately after (T2), and more than 1 year after (T3) surgery. Paired t -tests and Pearson’s correlation analysis were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 21 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…showed that the pharyngeal airway space is negatively affected after mandibular setback surgery after the long-term follow-up [2]. A previous study done by Kang et al demonstrated that mandibular setback surgery showed a significant reduction in pharyngeal airway compared to bimaxillary surgery (posterior impaction).…”
Section: Pharyngeal Airway Spacementioning
confidence: 93%
See 4 more Smart Citations
“…showed that the pharyngeal airway space is negatively affected after mandibular setback surgery after the long-term follow-up [2]. A previous study done by Kang et al demonstrated that mandibular setback surgery showed a significant reduction in pharyngeal airway compared to bimaxillary surgery (posterior impaction).…”
Section: Pharyngeal Airway Spacementioning
confidence: 93%
“…The oropharynx is divided into the retroglossal and retropalatal pharynx and separated by the soft palate. The tongue is the highest functioning part of the oropharyngeal structure and is affected by any alteration to the oro-dental system, particularly the mandible [ 2 ]. The changes in the position of hyoid bone are dependent on the resistance that is provided by the elastic membranes of the larynx and trachea and the action of supra-hyoid and infra-hyoid muscles [ 8 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations